EFEKTIVITAS RED NOTICE INTERPOL DALAM PENINDAKAN PENCUCIAN UANG OLEH KORPORASI GLOBAL: ANALISIS YURIDIS DAN DIPLOMASI PENEGAKAN - Sinambela, Kabet Neko; Purwati, Ani; Marina, Liza (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Law enforcement against perpetrators of transnational economic crimes faces serious challenges in the era of globalization, particularly concerning the escape of suspects or convicts abroad. Interpol, as an international police organization, plays a vital role in assisting national authorities through the Red Notice mechanism—a request to member states to locate and provisionally arrest a fugitive based on a request for extradition or legal proceedings. However, in practice, the effectiveness of Red Notices is often questioned due to legal loopholes, lack of harmonization in national regulations, and instances of misuse for political purposes. This study aims to examine the role of Interpol and Red Notices in handling fugitives of economic crimes, identify inherent legal weaknesses, and formulate reform recommendations to enhance the effectiveness and accountability of the national legal system. The methodology used is a normative legal approach combined with case study, statutory, and doctrinal analysis—specifically reviewing the Djoko Tjandra case as a representative example of legal and institutional issues. The analysis reveals that Indonesia requires stronger regulation and inter-agency coordination to ensure the use of Red Notices aligns with the principles of due process of law and does not violate the principle of non-refoulement. The recommendations proposed include the need to establish a more explicit legal framework for the implementation of Red Notices, enhance transparency in their issuance and withdrawal, and strengthen bilateral cooperation within the extradition framework. Through such reforms, Indonesia’s legal system is expected to become more responsive in addressing the challenges of global economic crime.